2018
DOI: 10.1136/bcr-2018-225571
|View full text |Cite
|
Sign up to set email alerts
|

Polypoidal lesions associated to choroidal naevus: spectrum of pachychoroid disease?

Abstract: A 78-year-old woman was referred by an optician for an incidental finding of peripapillary naevus in the absence of visual symptoms. On examination, the right eye showed a choroidal naevus of around 1.5 disc diameter, adjacent to the optic disc. Optical coherence tomography detected the presence of pigment epithelium detachment and subretinal fluid within the context of the naevus. Fundus fluorescein angiography and indocyanine green showed multiple polypoidal lesions (Polypoidal Choroidal Vasculopathy, PCV) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Further, such changes might result in the growth of Type 1 neovascular membranes and eventually in the development of PCV adjacent to the melanocytic lesion, as we have observed in this case series. In addition, another possible hypothesis would be the anecdotal association of PCV and choroidal nevus in the context of paquichoroid(Anzidei) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Further, such changes might result in the growth of Type 1 neovascular membranes and eventually in the development of PCV adjacent to the melanocytic lesion, as we have observed in this case series. In addition, another possible hypothesis would be the anecdotal association of PCV and choroidal nevus in the context of paquichoroid(Anzidei) [13].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient we were able to observe various causes and/or consequences of the ischemia and the mechanical microtrauma in the Bruch’s membrane, such as glaucomatous optic neuropathy, choroidal nevus and type 1 NV associated to PPS, which demonstrates that pathogenic mechanisms of retinal disorders are interrelated in most cases. 79 For all these findings, we present the PPN as a new clinical entity within PD, which we can see in some advanced cases of PPS.…”
Section: Discussionmentioning
confidence: 62%
“…7,8,14 In the presence of exudation, reported treatment included photodynamic therapy, 9,11 single intravitreal anti-VEGF injections, 13,14 or a combination of both. 10 After these treatments, improvement in visual acuity and resolution of leakage were observed in all reported cases, with a follow-up up to 2 years. A singular case reported success when using focal laser photocoagulation.…”
Section: Discussionmentioning
confidence: 81%
“…The first report about polypoidal lesions in association with choroidal nevi was published in 2009 by Peiretti et al 8 Since then, single cases have been reported. 9–15 Although many cases can be safely observed, some require treatment with intravitreal antivascular endothelial growth factor (VEGF) injections, 12,16 photodynamic therapy, 9,13 or focal argon laser. 14…”
mentioning
confidence: 99%
See 1 more Smart Citation